Landscape of Immune Microenvironment Under Immune Cell Infiltration Pattern in Breast Cancer - Xu, Qianhui; Chen, Shaohuai; Hu, Yuanbo; Huang, Wen (Frontiers in Immunology, 2021)
Background: Increasing evidence supports the suggestion that the immune cell infiltration (ICI) patterns play a pivotal role in tumour progression in breast cancer (BRCA). Nonetheless, there has been no comprehensive analysis of ICI patterns effects on clinical outcomes and immunotherapy. Methods: Multiomic data for BRCA samples were downloaded from TCGA. ESTIMATE algorithm, ssGSEA method and CIBERSORT analysis were used to uncover the landscape of the tumour immune microenvironment (TIME). BRCA subtypes based on ICI pattern were identified by consensus clustering and principal-component analysis was performed to obtain ICI scores to quantify the ICI patterns in individual tumors. Their prognostic value was validated by Kaplan-Meier survival curves. Gene set enrichment analysis (GSEA) was applied for functional annotation. Immunophenoscore (IPS) was employed to explore immunotherapeutic role of ICI scores. Finally, the mutation data was analyzed by using “maftools” R package. Results: Three different immune infiltration patterns with distinct prognosis and biological signature were recognized among 1198 BRCA samples. The characteristics of TIME under these three patterns were highly consistent with three known immune profiles: immune- excluded, immune-desert, and immune-inflamed phenotypes, respectively. The identification of ICI patterns within individual tumors based on ICI score, developed under the ICI-related signature genes, contributed into dissecting biological processes, clinical outcome, immune cells infiltration, immunotherapeutic effect and genetic variation. High ICI score subtype, characterized with suppression of immunity, suggested an immune-exhausted phenotype. Abundant effective immune cells were discovered in the low ICI score patients, which corresponding to an immune-activated phenotype and might presented immunotherapeutic advantage. Immunophenoscore was implemented as a surrogate of immunotherapeutic outcome, low-ICI scores samples obtained significantly higher immunophenoscore. Enrichment of JAK/STAT and VEGF signal pathways were activated in ICI low-score subgroup. Finally, the synergistic effect between the ICI score and the tumour mutation burden (TMB) was confirmed. Conclusion: This work comprehensively elucidated that ICI patterns served as an indispensable player in complexity and diversity of TIME. Quantitative identification of ICI patterns in individual tumor will contribute into mapping landscape of TIME further optimizing precision immunotherapy.